Peran Kelas Ibu Balita Terhadap Praktik Pemberian ASI Ekslusif - Hidayah, Luluk; Rosita, Devi (VISIKES: Jurnal Kesehatan Masyarakat, 2018)
Toddlerâs Mother Class has an important role in improving the coverage of exclusive breast feeding. The purpose of this study was to describe the role of the Toddlerâs Mother Class with exclusive breast feeding practice in Public Health Center of Godong I.This study used qualitative methods with snowball sampling techniques. The informant of the study are toddlerâs mother who have a child aged 6-12 months with total informant are ten informant. Collecting data technique with in-depth interviews and used interview guidelines.The results showed that implementation of Toddlerâs Mother Class was done three times a year by the facilitator, consists of a village midwives, public health centers midwives, and a nutritionist or dental expert or infectious disease control officer. Source of funding the activities derived from Special Operational Assistance (BOK), media health promotion used a sheet back, and targets were not grouped by age, but focused on toddlers who haved growing hibicus problems. Most of informants have knowledgeable about exclusive breast feeding and have agreed to give exclusive breast feeding. However, only a portion (50%) the informant can provide exclusive breast feeding to her baby, because the lack of support from the husband and family.Toddlerâs Mother Class at Public Health Center of Godong I was implemented in all of the village, but there was still mother of a baby who does not provide exclusive breast feeding.